Gender and Ethnicity in Vietnam Agroforestry Landscapes: Lessons for Project Implementation - Nguyen, M.P.; North, H.; Duong, M.T.; Nguyen, M.C. (World Agroforestry Centre, 2021)
The brief summarizes learnings and outcomes from the Agroforestry for Livelihoods (AFLi) project, implemented by World Agroforestry (ICRAF) in Northwestern Vietnam. The project took place in two phases over the period of 2011 to 2021, it sought to encourage farmers to adopt agroforestry systems to combat environmental degradation and to diversify their agricultural products. The second phase of the project (AFLi-II) focused on the development of market-based agroforestry and forest rehabilitation.